Föld és hatalom. A herceg Esterházy család uradalmainak változásai : 17-20. század - Kaposi, Zoltán (Közép-Európai Közlemények, 2014)
The traditional feudal form of the Esterházys’ land tenure underwent significant changes during the examined 400 years in the 17-20lh centuries. In the first 150 years it was pliantly adaptable to the changes without global importance of that age. Buti in the age of the bourgeois reforms the massive demand fór land ownership of the serfs, the challenges of running a modem economy and the prestigious princely lifestyle became more and more contradictory. By the early 1860s the fee tail went bankrupt and it could only be very slowly reformed. As a result of the various cataclysms of the 20,h century (Trianon, land reform, capital levy) a significant portion of the fee tail’s land estates were lost and finally the land reform of 1945 liquidated the priváté property of aristocrats: the farmlands were devided and the forests became State property. Today only wooded properties and lumbermills in Austria together with somé buildings and assets remain of the original system, bút this hardly resembles a traditional land estates.